Thalidomide induces mucosal healing in postoperative Crohn disease endoscopic recurrence: Case report and literature review. Issue 36 (September 2016) - Hu, Huiqin; Wang, Xinying; Liu, Side
Abstract: Background: Thalidomide has been successful use in patients with refractory Crohn disease (CD) in recent years. Methods: We collected the data of a postoperative CD patient who was prescribed thalidomide to induce remission and reviewed the relevant literatures. Results: A 51-year-old female was diagnosed as CD after an urgent terminal intestinal resection and presented endoscopic recurrence despite the prophylactic treatment with azathioprine (AZA). Fortunately, she achieved mucosal healing (MH) at a low dose of thalidomide for 15 months. Conclusion: Thalidomide is effective to induce MH in the postoperative CD endoscopic recurrence.